1984
DOI: 10.1002/chin.198411166
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: SYNTHESES AND PROPERTIES OF DIMETHYLDIPHENYLTETRADEHYDRO‐TRIDECA‐, ‐PENTADECA‐, HEPTADECA‐, NONADECA‐FULVENE, AND BENZANNULATED PENTADECAFULVENE DERIVATIVES

Abstract: Durch Reaktion der Annulenone (Ia)‐(IVa) mit aus der Essigsäure (V) gebildetem Diphenylketen lassen sich die roten Titelverbindungen (Ib)‐(IVb) herstellen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…The inner proton(s) of all of the fulvenes (18)-(21) resonate at rather low field compared with the outer protons in each case, reflecting the fact that the diacetylene moiety exerts a local anisotropic effect on the inner proton(s), as has been observed for the corresponding diphenyl series (3) and (4). 2 This observation also supports the supposition that these fulvenes do not possess a ring current. Therefore, it is concluded that the fulvene molecules (18)-( 21) are not significantly polarized by the presence of two chlorine atoms at the exocyclic double bond in the ground state.…”
Section: Resultssupporting
confidence: 69%
“…The inner proton(s) of all of the fulvenes (18)-(21) resonate at rather low field compared with the outer protons in each case, reflecting the fact that the diacetylene moiety exerts a local anisotropic effect on the inner proton(s), as has been observed for the corresponding diphenyl series (3) and (4). 2 This observation also supports the supposition that these fulvenes do not possess a ring current. Therefore, it is concluded that the fulvene molecules (18)-( 21) are not significantly polarized by the presence of two chlorine atoms at the exocyclic double bond in the ground state.…”
Section: Resultssupporting
confidence: 69%